THE USE OF THE DUOLINGO GUESSING GAME APPLICATION IN TEACHING SPEAKING ABILITY TOWARD 8TH - STUDENTS - Tengku Winona Emelia; Ambar Wulan Sari; Khaidir Khaidir (JGK (Jurnal Guru Kita), 2022)
The Use Of The Duolingo Guessing Game Application In Teaching Speaking Ability Toward 8th - Students. This study was aimed to analyze how students use the game application named Duolingo, as an English learning application, to evaluate its benefit to help students in learning English and to assess students' skills in speaking. The data for this research was collected by using post and pre-test methods in research techniques. The data source was students from SMP Muhammadiyah 1 Medan, focused on 8th grade by providing multiple-choice questions by using Duolingo Applications. The quantitative design was used in this study and the techniques for data analysis include (1) data collection procedures, (2) data analysis techniques, and (3) conclusions. Based on analysis findings, students provided improvements to English learning and they speak more smoothly with a better tone. However, learning English has a number of advantages, and since Duolingo is a form of multiple choice test so the students enjoy, and it help the problem of speaking and use repetition of words so the students can follow how to say or speak.